Planet Philippines - Flores, Marissa L.; Guidaya-Atienza, Angeli (GMA News and Public Affairs, 2008)
One of the most thought-provoking and comprehensive environmental documentaries ever seen on local television. Journeys into the best-kept secrets of the natural world where life and the amazing systems that support it are an everyday spectacle. It is an impressive compilation of moving images showcasing the country's finest natural treasures.